1995
DOI: 10.1128/jb.177.16.4593-4600.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Ser2 codon of the light-harvesting B870 alpha polypeptide of Rhodobacter capsulatus partially suppresses the pufX phenotype

Abstract: The exact function of the pufX gene product of Rhodobacter capsulatus is uncertain, but deletion of the pufX gene renders cells incapable of phototrophic growth on a minimal medium, and photosynthetic electron transfer is impaired in vitro. However, suppressor mutants that are able to grow phototropically are readily isolated. Two such suppressor mutants were characterized as to their phototrophic growth properties, their fluorescence at different incident light intensities, the integrity of their chromatophor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
20
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
7
20
0
Order By: Relevance
“…Furthermore, the third phase of the bandshift (compare the two panels of Fig. 5b) appeared to be reduced in MA05, suggesting that the reduced amount of RC in MA05 is impaired in quinol transfer from the RC to the cytochrome b/c 1 complex, which is characteristic of a PufX deficiency (28,29).…”
Section: The Entire Population Of Puhbmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, the third phase of the bandshift (compare the two panels of Fig. 5b) appeared to be reduced in MA05, suggesting that the reduced amount of RC in MA05 is impaired in quinol transfer from the RC to the cytochrome b/c 1 complex, which is characteristic of a PufX deficiency (28,29).…”
Section: The Entire Population Of Puhbmentioning
confidence: 98%
“…The puf operon is part of a superoperon that includes pigment biosynthesis genes (53) and also encodes PufQ, a regulatory factor in BChl biosynthesis (4). PufX has been implicated in the exchange of quinone/quinol between the RC and cytochrome b/c1 complexes (28,29).In this study, we investigate the basis of the RC/LH1 deficiency and impaired photosynthetic growth of R. capsulatus puhB disruption strains by examining the effects of PuhB on RC assembly in the absence of LH1, LH1 assembly in the absence of the RC, and the abundance of PufX. We also evaluate the ability of each of the three putative transmembrane (TM) segments of PuhB to span the inner membrane and to self-associate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures of the reaction center and light-harvesting (LH) integral membrane pigment-protein complexes from several species have been published (15,17,22). Although the structural proteins of these complexes are very hydrophobic and might be thought of as independently capable of complex assembly in the cytoplasmic membrane, several genes that do not encode crystal structural components and yet are required to obtain wild-type levels of the reaction center and LH complexes have been discovered (2,12,19,31). The results of preliminary experiments with one of these genes, F1696, indicate that it functions to enhance assembly of LH complex I (LHI) as opposed to inhibiting turnover (31a).…”
mentioning
confidence: 99%
“…sphaeroides . The finding was further supported by the localization of second-site suppressor mutants in the pufBA genes encoding the LH 1-α-and β-apoproteins (Lilburn et al 1995), and the lack of a PufX requirement in the absence of LH 1 as shown in Neil Hunter's laboratory (McGlynn et al 1994). These findings have suggested that in the absence of PufX, LH 1 tightly surrounds the reaction center and impedes UQ/UQH 2 movements and that the suppression of this defect results from a destabilization of LH 1, enhancing UQ exchange.…”
Section: The Assembly Of Supercomplexesmentioning
confidence: 73%